Oxidative Stress Modulation in Type 2 Diabetes: Insights from Metformin and Pioglitazone Therapy: Oxidative Stress in T2DM: Metformin and Pioglitazone - Varikasuvu, Seshadri Reddy (Journal of Medical Biochemistry, 2025)
This commentary critically examines a recent study that assessed the effects of metformin and pioglitazone on oxidative stress in patients with type 2 diabetes mellitus. The original study utilized multiple biomarkers such as IMA, TOS, TAS, and OSI but observed only limited antioxidant effects and a rise in IMA levels. By referencing additional clinical trials, experimental studies, and reviews, this commentary emphasizes the importance of using broader biomarker panels, extending treatment duration, and interpreting oxidative stress markers with caution in diabetes research.